2011
DOI: 10.1111/j.1439-0531.2011.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Gene Expression of Fn‐Type II and Cysteine‐Rich Secretory Proteins in the Reproductive Tracts and Ejaculated Sperm of Chinese Meishan Pigs

Abstract: Fibronectin type II and cysteine-rich secretory proteins have been well studied in the murine and human. The present study evaluated CRISP1, CRISP2, CRISP3 and Fn-type II (ELSPBP1 and pB1) gene expression patterns in ejaculated sperm and reproductive tracts of Chinese Meishan pigs from birth to day 150 of age. In ejaculated sperm, except for ELSPBP1, all others genes studied were detectable. In sexually mature boars and gilts, CRISP1 gene was expressed strongly in whole epididymides, moderate in prostate and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These data further support the concept that trophoblast can inhibit the expression of genes. CRISP3 is widely expressed in the reproductive tract of males [43] and females [5] , [44] with several functions attributed to it including a supporting role in localized tissue inflammation and immune response [45] , [46] . It is therefore not surprising that pathway analysis confirmed pathways regulated by local trophoblast to include those involved in immune function and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These data further support the concept that trophoblast can inhibit the expression of genes. CRISP3 is widely expressed in the reproductive tract of males [43] and females [5] , [44] with several functions attributed to it including a supporting role in localized tissue inflammation and immune response [45] , [46] . It is therefore not surprising that pathway analysis confirmed pathways regulated by local trophoblast to include those involved in immune function and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pittoggi and coworkers found that the transcription and splicing activities are occasionally initiated in mature sperm (Pittoggi et al 2006). Moreover, a very high abundance of sperm adhesins and most CRISP and Fn-type II mRNAs were found in ejaculated sperm, most of which exhibited weak or no expression in the testes (Song et al 2010(Song et al , 2011. A comparative analysis of the transcripts between bovine spermatids and mature sperm also revealed that although 36.81% were common in both cell types, only 4.5% were specific to mature sperm (Gilbert et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the RNA samples were subjected to purity qualification by RT-PCR amplification of CD4, E-cadherin and c-kit, which are markers of leukocytes, epithelial cells and testicular germ cells respectively, as described previously (Song et al 2011). GAPDH and AQN-3 were used as positive controls for sperm RNA and testis cDNA.…”
Section: Small Rna Library Construction and Sequencingmentioning
confidence: 99%
“…The expression of CRISP2 was down-regulated in patients with teratoasthenozoospermia, asthenozoospermia or teratozoospermia (16). Contrary to the knowledge gained from mice and humans, the function of CRISP2 in pig reproduction is poorly characterized except for the mRNA expression in reproductive organs (8,17).…”
mentioning
confidence: 89%